Increasing Resistance To High Temperatures In Mortars Using A Variety Of Ingredients Added Palm Sugar - Neri Puspita Sari (Program Studi Teknik Sipil Sekolah Tinggi Teknologi Pekanbaru, 2022)
Preparation of test specimens was carried out to determine the dose of palm sugar using a cement water factor of 48, with variations in the addition of palm sugar doses, namely: 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5 %, and 0.6 %, with 28 days of curing at room temperature (without immersion), the specimens were subjected to heating temperatures of C., C. and C. that at 250 0C a dose of 0% has the highest compressive strength, each additional dose of palm sugar decreases in compressive strength, at 500 0C a dose of 0% has the highest compressive strength, the decrease in compressive strength does not occur significantly at dose 0, 1%, 0.2%, 0.3% and 0.4% decreased significantly at doses of 0.5% and 0.6%, on heating to 750 0C a dose of 0.1% has the highest compressive strength at a dose of 0.2% and 0.3% compressive strength is still above 10 Mpa.